Genetic variation and genomic constitution in orchid Dendrobium hybrid section Spatulata derived from interspecific hybridization based on sequence related amplified polymorphism marker - Aziz Purwantoro; Agus Budi Setiawan; Sairoh Bisirotil Mujtaba; Aditya Hanung Setyadi; Rikcy Setiaji Nugraha (Universitas Gadjah Mada, 2023)
Dendrobium hybrid section Spatulata is widely cultivated in Indonesia due to its ease of cultivation, high economic value and adaptability, also extended flower shelf life. Various attempts to meet the rising market demand for Dendrobium hybrid section Spatulata, including the development of new varieties with unique flower traits such as flower color, a longer and bigger horn, and disease resistance. In this study, we conducted a breeding program aimed at developing a new cultivar of Dendrobium hybrid section Spatulata (antelope orchids) through interspecific hybridization. The study aimed to investigate the genetic variation and genomic constitution of the eight hybrids and their corresponding parental lines that resulted from interspecific hybridization using sequence‐related amplified polymorphism (SRAP) marker. Six species of Dendrobium section Spatulata i.e., Dendrobium Sri Mulyani, D. Cochliodes, D. strepsiceros, D. stratiotes, D. Alice Noda, D. helix, and several hybrids of antelope orchids derived from three hybridizations including D. Sri Mulyani × D. cochliodes, D. stratiotes × D. strepsiceros, and D. Alice Noda × D. helix, respectively, were subjected into SRAP markers for genotyping analysis. Dendrobium hybrid section Spatulata hybrids produced by interspecific hybridization were genuine hybrids with substantial genetic variability based on flower morphology, including labellum shapes and color intensities, as well as curly horn shapes and color intensities. The SRAP marker, which was used to genotype the hybrid and parental lines, exhibited a significant degree of polymorphism, and might be used to distinguish each accession. It produced a unique DNA amplicon that ranged from 180 to 530 bp and inherited a certain progeny line. The unweighted pair group mean average (UPGMA) dendrogram and Principal Coordinate Analysis (PCoA) biplot showed that all the hybrids were grouped into three major clusters according to their corresponding parental lines based on their genetic background and ge‐ nomic constitution. These findings are critical for the genetic improvement of the Antelope orchid to develop novel varieties.